Genomic analysis of two phlebotomine sand fly vectors of Leishmania from the New and Old World - Labbé, Frédéric; Abdeladhim, Maha; Abrudan, Jenica; Araki, Alejandra Saori; Araujo, Ricardo N; Arensburger, Peter; Benoit, Joshua B; Brazil, Reginaldo Pecanha; Bruno, Rafaela V; Bueno da Silva Rivas, Gustavo; Carvalho de Abreu, Vinicius; Charamis, Jason; et al. (PLoS neglected tropical diseases, 2023)
Phlebotomine sand flies are of global significance as important vectors of human disease, transmitting bacterial, viral, and protozoan pathogens, including the kinetoplastid parasites of the genus Leishmania, the causative agents of devastating diseases collectively termed leishmaniasis. More than 40 pathogenic Leishmania species are transmitted to humans by approximately 35 sand fly species in 98 countries with hundreds of millions of people at risk around the world. No approved efficacious vaccine exists for leishmaniasis and available therapeutic drugs are either toxic and/or expensive, or the parasites are becoming resistant to the more recently developed drugs. Therefore, sand fly and/or reservoir control are currently the most effective strategies to break transmission. To better understand the biology of sand flies, including the mechanisms involved in their vectorial capacity, insecticide resistance, and population structures we sequenced the genomes of two geographically widespread and important sand fly vector species: Phlebotomus papatasi, a vector of Leishmania parasites that cause cutaneous leishmaniasis, (distributed in Europe, the Middle East and North Africa) and Lutzomyia longipalpis, a vector of Leishmania parasites that cause visceral leishmaniasis (distributed across Central and South America). We categorized and curated genes involved in processes important to their roles as disease vectors, including chemosensation, blood feeding, circadian rhythm, immunity, and detoxification, as well as mobile genetic elements. We also defined gene orthology and observed micro-synteny among the genomes. Finally, we present the genetic diversity and population structure of these species in their respective geographical areas. These genomes will be a foundation on which to base future efforts to prevent vector-borne transmission of Leishmania parasites.
Keywords: genomika; Phlebotomus; Animals; Leishmaniasis, Cutaneous; lidé; leishmanióza kožní; Humans; zvířata; Leishmania; Psychodidae; Genomics